Semiotic Analysis of Profit Sharing in Islamic Finance: A Critical Study of Roland Barthes - Cahya, Bayu Tri; Azliani, Firda Nur; Mohd Ali, Nor Aishah; Saputri, Dilla Ajeng Diah; Marpaung, Muslim (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
Within the context of Islamic finance, profit sharing represents more than a mere economic mechanism, yet its deeper symbolic meanings remain underexplored. This study aims to uncover the layered meanings of profit sharing through denotation, connotation, and myth using Roland Barthes's semiotic framework. Employing a qualitative approach with a postmodernist perspective, data were collected through field research involving in-depth interviews with nine informants, supplemented by secondary literature reviews. The findings reveal that profit sharing operates on three semiotic levels: denotatively as cooperation and mutual agreement; connotatively as mutual assistance, responsibility, and rejection of injustice reflecting the Prophet Muhammad SAW's example; and mythologically as connected to the traditional